Enhancing Critical Thinking in Analyzing Short Story “The Lazy Jack” Viewed from Identity Theory - Moh. Yamin; Ajah Saputra; Nurhamsi Deswila (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This paper aims to describe and discuss the messages and meanings of the short story “The Lazy Jack”. The significance of this research is for building new frame that analyzing literary work is only viewed from the setting or character in a simple manner, but also can be viewed from identity theory assisted with critical thinking as the thinking approach rationally and based on the reason. The basis of reasoning is based on the researchers’ capacity in deepening and learning the situations and conflict happening to the character in the story. It is qualitative research in which the data collection is started from coding obtained from the text “The Lazy Jack” in line with the goal of the research. The result of this research shows that Jack does not have a firm personal identity, firm life principle, life vision, and struggling for survival. He is the one dependent on others although he always fails to learn to be better. It means that Jack is without personal and social identity.